2014
DOI: 10.1136/sextrans-2014-051715
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the costs and outcomes of sexually transmitted infection (STI) screening interventions targeting men in football club settings: preliminary cost-consequence analysis of theSPORTSMARTpilot randomised controlled trial

Abstract: BackgroundThe objective of this study was to compare the costs and outcomes of two sexually transmitted infection (STI) screening interventions targeted at men in football club settings in England, including screening promoted by team captains.MethodsA comparison of costs and outcomes was undertaken alongside a pilot cluster randomised control trial involving three trial arms: (1) captain-led and poster STI screening promotion; (2) sexual health advisor-led and poster STI screening promotion and (3) poster-onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Table 1 provides an overview of the main characteristics of the 31 studies identified for inclusion. The main countries where the studies took place were the Netherlands (7) [21][22][23][24][25][26][27], UK (8) [28][29][30][31][32][33][34][35], and United States of America (12). The majority of studies compared the costeffectiveness or cost-utility of two or more different screening options for chlamydia (25 studies).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 provides an overview of the main characteristics of the 31 studies identified for inclusion. The main countries where the studies took place were the Netherlands (7) [21][22][23][24][25][26][27], UK (8) [28][29][30][31][32][33][34][35], and United States of America (12). The majority of studies compared the costeffectiveness or cost-utility of two or more different screening options for chlamydia (25 studies).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The majority of studies compared the costeffectiveness or cost-utility of two or more different screening options for chlamydia (25 studies). Six studies included gonorrhoea screening in their strategy [28,[36][37][38] and one focussed on the cost-effectiveness of age-specific HIV screening. [39] The search did not identify any study assessing interventions for syphilis.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent study of routine repeat screening in the Netherlands reported screening costs of £100 per-screen (inflated and converted from 2014 data) [22]. A community CT screening study in England aimed at men attending sports clubs estimated that costs ranged from £92 to £100 per screen (inflated from 2013 estimates) with no CT infections detected [23].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%